2003
DOI: 10.1097/01.brs.0000076895.52418.5e
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Lumbar Fusion

Abstract: Preliminary clinical results suggest that minimally invasive lumbar fusion will have a beneficial impact on the care of patients with spinal disorders. Outcome studies with long-term follow-up will be necessary to validate its success and allow minimally invasive lumbar fusion to become more widely accepted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
364
1
18

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(421 citation statements)
references
References 39 publications
6
364
1
18
Order By: Relevance
“…The advantages associated with MI-TLIF might be attributed to less intraoperative dissection and retraction of paravertebral muscles [1,2,5]. Shunwu et al [6] found the minimally invasive group was associated with a significantly lower creatine kinase (a marker of muscle injury) level on the third postoperative day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages associated with MI-TLIF might be attributed to less intraoperative dissection and retraction of paravertebral muscles [1,2,5]. Shunwu et al [6] found the minimally invasive group was associated with a significantly lower creatine kinase (a marker of muscle injury) level on the third postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns are often associated with the stripping of paravertebral muscles [1,2]. To address these problems, Foley et al [5] described an alternative technique: minimally invasive TLIF (MI-TLIF). MI-TLIF was developed with the advancement of modern surgical instrumentation and optical systems [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, many authors have reported the advantages of the mini-invasive posterior lumbar approach versus the conventional open procedures such as the reduction of intra-operative blood loss, less damage to soft tissues, relief of postoperative pain, early mobilization of the patient, shorter hospital stay, and a rapid return to an active social and working life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Transforaminal lumbar interbody fusion utilizes a unilateral approach that allows for simultaneous neural canal decompression with an anterior interbody arthrodesis through a single posterior incision [8,11]. This procedure diminishes neural retraction and reduces the risk of neural injury compared with bilateral posterior lumbar interbody fusion [8,12,28].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure diminishes neural retraction and reduces the risk of neural injury compared with bilateral posterior lumbar interbody fusion [8,12,28]. It is possible to perform unilateral posterior surgery using less invasive approaches to neural decompression and intervertebral arthrodesis through a tubular retractor and by augmenting the fusion construct with percutaneous pedicle screw instrumentation.…”
Section: Introductionmentioning
confidence: 99%